Drug usage pattern of antimicrobials in elderly hypertensive, diabetic in-patients with or without impaired renal function - Bhandari, Prasan R.; Bhandary, Apeksha (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Hypertension (HTN) and diabetes mellitus (DM) are the primary contributors to renovascular mortality and morbidity including chronic kidney diseases. Additionally, these patients are in frequent need of an antimicrobial agent. Drug utilisation studies (DUS) are prospective tools in the assessment of health care systems. The objective of the present study was to analyse the prescription pattern of anti-microbials in elderly hypertensive diabetic in-patients with or without renal impairment in a tertiary hospital Methods: The study population comprised of 165 hypertensive diabetic in-patients at Shri Dharmasthala Manjunatheshwara (SDM) Hospital. Questionnaire based evaluation was carried out and prescriptions of patient with HTN and DM at and above the age of 60 years irrespective of gender were included. Results: Among anti-microbial agents, other β lactam antibacterial were the most commonly prescribed class of drugs (40.85%) which was similar in patients with impaired renal function (21.8%). Conclusions: There was a significant increase in the number of anti-microbial agents and other drugs in the patients with impaired renal function when compared to patients with normal renal function (p <0.05).